1973
DOI: 10.1177/001440297303900703
|View full text |Cite
|
Sign up to set email alerts
|

The Measurement of Attentional Deficits

Abstract: A new methodological procedure has been developed based on the vigilance task for investigating attentional deficits. The subject is directed to respond to visual signals which occur randomly within a temporal sequence of visual events noted as a pattern of flashing lights. The procedures successfully differentiate between children with learning disabilities and normal control subjects. The procedure allows attentional deficits in children to be studied in such a way as to bring variables not previously contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
19
0
1

Year Published

1979
1979
1992
1992

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(24 citation statements)
references
References 2 publications
4
19
0
1
Order By: Relevance
“…A wide variety of clinically disordered groups of children have been studied with the CPT including hyperactive (Sykes, Douglas, & Morgenstern, 1973), learning disabled (Anderson, Halcomb, & Doyle, 1973;Swanson, 1981Swanson, , 1983, behaviorally deviant (Kupietz, 1976), children at risk for schizophrenia (Rutschmann, Cornblatt, & Erlenmeyer-Kimling, 1986), educationally handicapped (Keogh & Margolis, 1976a) and retarded readers (Noland & Schuldt, 1971). Children from these groups usually display poor sustained attention including fewer correct detections, a higher rate of false alarms, and often a more rapid deterioration over time when compared with matched normal controls.…”
Section: Sustained Attentionmentioning
confidence: 99%
“…A wide variety of clinically disordered groups of children have been studied with the CPT including hyperactive (Sykes, Douglas, & Morgenstern, 1973), learning disabled (Anderson, Halcomb, & Doyle, 1973;Swanson, 1981Swanson, , 1983, behaviorally deviant (Kupietz, 1976), children at risk for schizophrenia (Rutschmann, Cornblatt, & Erlenmeyer-Kimling, 1986), educationally handicapped (Keogh & Margolis, 1976a) and retarded readers (Noland & Schuldt, 1971). Children from these groups usually display poor sustained attention including fewer correct detections, a higher rate of false alarms, and often a more rapid deterioration over time when compared with matched normal controls.…”
Section: Sustained Attentionmentioning
confidence: 99%
“…This situation comprises what is known in the psychological literature as vigilance; typically vigilance tasks are signal detection tasks maintained for 30 minutes or more, in which signals are presented infrequently and without warning, and using stimuli which, although they may be detected without error in a twoalternative, forced-choice decision, are perceived by subjects as being weak, or not particularly "attention-demanding" (Anderson et al 1973), The vigilance task, like the industrial and military monitoring tasks on which it was modeled, typically yields a decline in detection performance over time known as the vigilance decrement; the crucial question regarding this phenomenon for purposes of the present review is whether children labeled "learning disabled" differ from normals in their vigilance performance.…”
Section: Vigilancementioning
confidence: 99%
“…learning disabled children have frequently been found to make both fewer correct detections and more false alarms than normals (Anderson et al 1973, Kirchner & Knopf 1974, Noland & Schuldt 1971; (3.) when hyperactive children are analyzed independently from a more inclusive LD group, most of the difference in accuracy between LDs and normals can be attributed to the hyperactivity subgroup (Doyle et al 1976, Anderson et al 1973; (4.) the vigilance decrement, or rate of performance decline over time, does not appear to differ in LDs and normals (Noland & Schuldt 1971); (5.)…”
Section: Vigilancementioning
confidence: 99%
“…Many studies have found a relationship between learning disabilities and attention deficit (Anderson, Halcomb, & Doyle, 1973;Koppell, 1973;Tarver & Hallahan, 1974;Vrana & Pihl, 1980), whereas other studies have found no significant attentional difficulties in LD samples (Lovrich & Stamm, 1983;Pelham, 1979;Swanson, 1981Swanson, ,1983. It is difficult to reconcile these conflicting results.…”
mentioning
confidence: 96%
“…For example, Anderson, Halcomb, and Doyle (1973) found that LD children made more errors (fewer correct detections and more false alarms) than controls on the CPT and interpreted the results as evidence of attentional deficits in the LD group. However, from the signal detection perspective, the LD children would not be considered as attention impaired, but as low risk takers and as exhibiting a reduced discriminative capacity from the onset.…”
mentioning
confidence: 99%